Eco-Syntax Analysis of Jameel Akhtar’s Short Story “ٹوٹی ہوئی سڑک” - Shaikh, Naila; Memon, Adnan Ahmed; Jumani, Ayesha (Pakistan Languages and Humanities Review, 2025)
This study examined the eco-syntax structures of the short story “ٹوٹی ہوئی سڑک” written by Muhammad Jameel Akhtar. In the examination of this short study, the eco-syntax structures were analyzed by using Labov’s model presented in 1972 on Natural Narratives. The narrative structures and the techniques used in the language highlighted the inherent connection between the natural environment and the characters of the story. It focused on the six elements of Labov’s model Abstract, Orientation, Complication, Evaluation, Resolution, and Coda where their eco-syntax structures were analyzed. The application of Labov’s model to written narratives brings out the cognitive-linguistic functioning into the act that helps to understand the impact of one action on others. The results of this study revealed how literary text’s understanding was enhanced through the narratives and the connection of humans with the natural world.